Peningkatan Pemahaman Tentang Garis Tinggi Pada Segitiga Dengan Pembelajaran Konstruktivisme (Studi Kasus Pada Mahasiswa Dual Mode Konsentrasi IPS, UPI Kampus Serang) - Isrok’atun Isrok’atun (Jurnal Fourier, 2012)
Knowledge is the student’s construction result that affect to the more meaningful learning. Sometimes, teachers forget that a student has self-live experiences as their initial concept. When expressed their initial concept, students will be easier to accept new material knowledge, because students will constructing their knowledge indirectly. The constructivism of learning is a teaching and learning process to make students themselves mentally active to construct their knowledge, based on cognitive structure that they ever had before. In the relationship to the student’s geometry concept, it must be considered how the students constructing this concept by their cognitive structure. Memorizing the mathematical formulation is not the guarantee that the students have been mastering to the real geometry. For example, to understand about height line in the triangle, is not an instantaneous process. It can be learned by constructing through an experiment to involving all student hands on activity process. Through the activity to make a height line, measuring, and calculating the triangle area, student will be led on the joyful activity, avoid to the bored, toward the conclusion that every triangle, there are three height lines for the three triangle’s bases in each area.